Transesterification process of Moringa oleifera oil to biodiesel - Kabbashi, Nassereldeen Ahmed; Hunud, Yara; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed; Jazzar, Moneef M. (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Biodiesel has become one of the leading options to replace fossil fuels as a source of energy. However, biodiesel production traditionally uses edible plants as it has high acid values, which in turn produce high quality oil. Moreover, current methods of producing biodiesel generate toxic waste as a result of chemical catalysts used to accelerate the process. Hence, this study was performed to explore the biodiesel potential of mature Moringa oleifera seeds, which are non-edible and therefore do not compete with food resources, via transesterification using immobilised Candida antarctica lipase as a catalyst. Moringa oil was extracted using Soxhlet extraction, with hexane as the solvent of choice. Candida antarctica lipase was then purified and immobilised on functionalised activated carbon (FAC) in order to enhance the activity and effectiveness of the enzyme. Effectiveness of different acids for functionalisation on immobilisation capacity was tested by reflux with hydrochloric acid, nitric acid and sulphuric acid, with hydrochloric acid FAC (HCl-FAC) giving the highest immobilization capacity (6.022 U/g). The optimum conditions were found to be 40°C, pH 6 and 24 hours. Next for process optimization, one factor at a time (OFAT) was used once more to determine if agitation, time, temperature, catalyst concentration and methanol to oil ratio showed significant influence on biodiesel production. Design Expert software (7.0.0) was used in order to determine the optimum conditions for transesterification of Moringa oil. FCCCD using Response Surface Methodology (RSM) was selected, and the parameters chosen were: methanol to oil ratio, temperature, catalyst concentration and time. The optimum conditions were found to be methanol to oil ratio 4:1, 40°C, 4% catalyst loading and 24 hours which gives a maximum yield of biodiesel of 94.01%. The kinetics of the transesterification reaction found that the activation energy was 43.126 kJ/mol and the frequency factor was 1.758 × 108 min-1 from a pseudo-first order reaction rate.